IMPACT OF QUOTA SYSTEM AND FEDERAL CHARACTER PRINCIPLE ON EMPLOYEE PERFORMANCE IN PUBLIC SECTOR: A STUDY OF ABIA STATE OIL PRODUCING AREA DEVELOPMENT COMMISSION - Onyeiwu, Emmanuel Anayo (African Journal of Social and Behavioural Sciences, 2024)
This study examined the impact of quota system and federal character principle, on public sector employee performance with a particular focus on the Abia State Oil Producing Area Development Commission. Three research objectives, three research questions and three research hypotheses guided the study. The researcher used the structural functional theory to analyse the subject matter. A survey research design was adopted and a questionnaire served as the instrument of data collection. The data collected were analysed using simple parentage and Pearson product-moment correlation coefficient to analyse the data collected. The findings revealed a significant relationship between the federal character principle and appointment, quota system and federal character principle affect employee promotion and there is a significant relationship between the federal character principle and employee retirement. Based on the findings, it was recommended that recruitment and appointments in all government establishments should be done based purely on qualification, experience, capabilities and professionalism. Furthermore, promotion, responsibility/position, training and re-training in such government establishments should be purely based on merit, inputs and contribution to service.